Radiolabeled Iron Oxide Nanoparticles As Dual-Modality SPECT/MRI and PET/MRI Agents - Bouziotis, P.; Psimadas, D.; Tsotakos, T.; Stamopoulos, D.; Tsoukalas, C. (CURRENT TOPICS IN MEDICINAL CHEMISTRY, 2012)
Dual-modality contrast agents, such as radiolabeled nanoparticles, are promising candidates for a number of diagnostic applications, since they combine the advantages of two different imaging modalities, namely SPECT or PET imaging with MR imaging. The benefit of such a combination is to more accurately interpret disease and abnormalities in vivo, by exploiting the advantages of each imaging technique, i.e. high sensitivity for SPECT/PET, high resolution anatomical information for MRI. In this review article, we provide an overview of recent findings in the synthesis, evaluation and application of radiolabeled iron oxide nanoparticles as dual-modality SPECT/MRI and PET/MRI imaging probes.